Parallel morpho-orthographic and morpho-semantic activation in processing second language morphologically complex words: Evidence from Chinese-English bilinguals. (June 2017) - Zhang, Qingge; Liang, Lijuan; Yao, Panpan; Hu, Shanshan; Chen, Baoguo
Objectives/research questions: The present study focused on the performance of Chinese learners of English to investigate the activation of morpho-semantic information in the early processing of second language (L2) morphologically complex words when participants' first language (L1) and L2 are typologically different. Methodology: We used forward masked priming paradigm to compare the priming effect in three prime conditions, semantically transparent, semantically opaque and semantically related. In Experiment 1, the stimulus onset asynchrony (SOA) was 40 milliseconds (ms), while, In Experiment 2, the SOA was extended to 80 ms. Data and analysis: Reaction time and comprehension accuracy data were analysed using the linear mixed-effects model. Findings/conclusions: In Experiment 1, we only found a priming effect in the semantically transparent condition. In Experiment 2, we found a reliable priming effect in the semantically opaque condition, but not in the semantically related condition. These results suggest even Chinese learners of English whose native language is typologically different from English can employ the rule-based decomposing mechanism. The decomposition is based on the interplay of morpho-orthographic and morpho-semantic information, adding new evidence to the assumption of parallel orthography-semantics activation. Originality: We manipulated SOAs to investigate the role of the morpho-semantic factor in the early processing of morphologically complex L2 words when participants' L1 and L2 are typologically different.